Tolong pliss yang jago mm

Posted on

1)

2x + y = 3 >> y = 3 – 2x

x – z = -1 >> z = x + 1

3y + z = -5

3(3 – 2x) + (x + 1) = -5

9 – 6x + x + 1 = -5

-5x + 10 = -5

-5x = – 15

X = -15/-5

X = 3

y = 3 – 2x

y = 3 – 2(3)

Y = 3 – 6

Y = -3

Maka x+y = 3 + (-3) = 0

2)

X + y = 5 >> x = 5 -y

Y + 4z = -1 >> y = -1 -4z

X + y + 3z = 2

(5-y) + (-1 – 4z) + 3z = 2

5 – y -1 – 4z + 3z = 2

5 – (-1 -4z) – 1 – 4z + 3z = 2

5 +1 + 4z – 1 – 4z + 3z = 2

5 + 3z = 2

3z = 2-5

3z = -3

Z = 0

Leave a Reply

Your email address will not be published. Required fields are marked *

Tolong pliss yang jago mm

Posted on

1)

2x + y = 3 >> y = 3 – 2x

x – z = -1 >> z = x + 1

3y + z = -5

3(3 – 2x) + (x + 1) = -5

9 – 6x + x + 1 = -5

-5x + 10 = -5

-5x = – 15

X = -15/-5

X = 3

y = 3 – 2x

y = 3 – 2(3)

Y = 3 – 6

Y = -3

Maka x+y = 3 + (-3) = 0

2)

X + y = 5 >> x = 5 -y

Y + 4z = -1 >> y = -1 -4z

X + y + 3z = 2

(5-y) + (-1 – 4z) + 3z = 2

5 – y -1 – 4z + 3z = 2

5 – (-1 -4z) – 1 – 4z + 3z = 2

5 +1 + 4z – 1 – 4z + 3z = 2

5 + 3z = 2

3z = 2-5

3z = -3

Z = 0

Leave a Reply

Your email address will not be published. Required fields are marked *